Cobalt boron nitride: A novel heterogeneous catalyst for the synthesis of medicinally important α-amino quinoline phosphonates. (2nd July 2016) - Sureshkumar, M.; Anand, K.; Muthu, T.; Gengan, R. M.
GRAPHICAL ABSTRACT: ABSTRACT: A novel cobalt supported on boron nitride (CoBNT) heterogeneous catalyst for the synthesis of α-amino quinoline phosphonates (AQPs) is reported in the present work. The CoBNT was synthesised by simply mixing boron nitride in a solution of cobalt acetate, under an inert atmosphere for 7 d followed by filtration; the yield was 94%. It exhibited excellent catalytic properties for the synthesis of 16 novel AQPs in a one pot mixture containing 2-methoxy 3-formyl quinoline, aniline derivatives and diethyl phosphite. Reactions were rapid, products were easily worked-up and were obtained in more than 90% yield. The CoBNT also exhibited higher catalytic activity than conventional catalysts and was re-used five times without significant decrease in catalytic activity.